American Girl. Grace stirs up success [videorecording (DVD)] - Marcello, Vince; Rodrigo, Olivia; Webb, Eloise; Carmichael, Caitlin, 2004- (Universal Studios Home Entertainment, 2015)
Grace has a real talent for baking and a passion for making delicious dreams come true. When her mom announces a trip to visit relatives in Paris, Grace isn't so sure about leaving her friends and their cupcake business.